Plant Colonization of Green Roofs Is Affected by Composition of Established Native Plant Communities - Aloisio, Jason M.; Palmer, Matthew I.; Tuininga, Amy R.; Lewis, James D. (Frontiers in Ecology and Evolution, 2019)
Human activities associated with urbanization have negatively affected the biodiversity of native plant communities globally. Establishing native species assemblages on green roofs may help conserve native plant diversity in urban areas, but these assemblages are susceptible to colonization by species from the surrounding landscape. In natural communities, colonization from the regional species pool reflects the filtering effects of both abiotic and biotic factors, but the relative effects of these factors on green roof colonization are not well understood. To address this knowledge gap, we studied colonization dynamics of 10 green roofs in New York City (NY, USA), each with 12 split-plots planted with an erect C4 graminoid dominant (Hempstead Plains: HP) and a tuft C3 graminoid and forb dominant (Rocky Summit: RS) species assemblage derived from native communities. Six of the 12 plots contained shallow growing medium, while the other six contained deeper growing medium. Resident plants were planted in May 2010. Fifty-eight non-resident plant species colonized plots between August 2011 and August 2012, with two native and 10 non-native species accounting for 90% of total colonist dry mass. Colonist dry mass and richness decreased with increasing resident plant cover, but the effects of growing medium depth on colonist dry mass and richness differed between assemblages. Forbs accounted for 81% of the colonist dry mass from the HP assemblage, but just 31% in the RS assemblage. Further, forbs accounted for over 95% of colonist dry mass in June and July, while graminoids accounted for over 95% of colonist dry mass in August. These results indicate colonization of planted green roofs may be strongly affected by the composition of established plant assemblages and that these effects may vary temporally, even within a single growing season. Further, the inconsistent effects of growing medium depth suggest that niche overlap and complementarity in rhizosphere dynamics may influence colonization more in some systems compared with others. Additional research is required to describe the effects of colonist management strategies, as well as the roles of priority effects, niche complementarity and community assembly, on long-term dynamics of colonization on green roofs planted with native plants.